2012
DOI: 10.1166/jnn.2012.5792
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Capped TiO2 Nanocrystals of Controlled Shape and Their Use with MEH-PPV to Develop Nanocomposite Films for Photovoltaic Applications

Abstract: The present study presents the synthesis details of titanium dioxide (TiO2) nanoparticles (NPs) of different morphologies using oleic acid (OA) and oleyl amine (OM) as capping agents. Different shapes of NPs, such as nanospheres, nanorods, and nanorhombics, were achieved. In order to develop nanocomposite thin films for photovoltaic cells, these TiO2 NPs were carefully dispersed in 2-methoxy-5-(2'-ethylhexyloxy)-p-phenylene vinylene (MEH-PPV) matrix. The properties of synthesized TiO2 NPs and MEH-PPV/TiO2 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The FTIR bands at 2850-2920 cm -1 are attributed to the asymmetric and symmetric C-H stretching vibrations of methylene groups, the vibration at 1465 cm -1 is a characteristic of -(CH 2 ) n -chains with n > 3, the small peaks at 3004 cm -1 correspond to the stretching of C-H bond [27][28][29]. Furthermore, it was observed that the vibration bands at 1710 and 1285 cm -1 , which are the characteristic bands of carbonyl -C = O-and -C-O-stretch in the carboxyl Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/25/15 6:27 PM results are all in agreement with those already obtained in our previous work [21]. In addition, according to the TGA spectrum, the amount of water absorbed on the surface of TiO 2 nanoparticles, which was already observed above by FTIR characterization, was around 1.4% for OA-OMcapped-TiO 2 and 3.5% OA-6AHA-capped-TiO 2 .…”
Section: Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…The FTIR bands at 2850-2920 cm -1 are attributed to the asymmetric and symmetric C-H stretching vibrations of methylene groups, the vibration at 1465 cm -1 is a characteristic of -(CH 2 ) n -chains with n > 3, the small peaks at 3004 cm -1 correspond to the stretching of C-H bond [27][28][29]. Furthermore, it was observed that the vibration bands at 1710 and 1285 cm -1 , which are the characteristic bands of carbonyl -C = O-and -C-O-stretch in the carboxyl Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/25/15 6:27 PM results are all in agreement with those already obtained in our previous work [21]. In addition, according to the TGA spectrum, the amount of water absorbed on the surface of TiO 2 nanoparticles, which was already observed above by FTIR characterization, was around 1.4% for OA-OMcapped-TiO 2 and 3.5% OA-6AHA-capped-TiO 2 .…”
Section: Characterizationsupporting
confidence: 91%
“…OA, OM or 6AHA capped anatase TiO 2 nanorods were synthesized at low temperature by the hydrolysis of TB using OA and OM or 6AHA as surfactants followed by the steps that we already described in our previous work [21,22]. Typically, 1 mmol of TB was added to a mixture of 7 mmol of OA, 3 mmol of OM or 6AHA, and EtOH.…”
Section: Synthesis Of Oa and Om Or 6aha Capped Tio 2 Nanorodsmentioning
confidence: 99%
“…A major role in shape and size control is also played by the OA/OM surfactants ratio, as both OA and OM exhibit selective binding forces for certain crystallographic faces of the TiO 2. OA specifically binds to TiO 2 (001) face and restricts the growth in the (001) direction, while OM promotes binding to the (101) crystalline face. However, when the ratio of OA is high (6/4 and 7/3 in our case), the adsorption on (001) faces is saturated resulting in the adsorption of OA on TiO 2 (101) faces .…”
Section: Resultsmentioning
confidence: 76%
“…The TGA curve of OA‐OM capped TiO 2 nanorhombic (Figure A) shows an initial weight loss of around 3 wt% starting from 50°C, which corresponds to the water absorbed on the surface of TiO 2 nanoparticles. The major weight loss occurring between 200°C and 480°C is attributed to the presence of OA and OM on the surface of TiO 2 nanorhombic, as already observed in literature . The weight loss corresponding to OA and OM surfactants calculated from the TGA curve is about 32 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation